2012
DOI: 10.4028/www.scientific.net/kem.517.556
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulosic Composites Made from Agricultural and Forestry Wastes in Brazil

Abstract: The Brazilian market of wood panels is in a consolidation process and presents great dynamism, which requires the search for new alternative raw materials that may contribute in quantity and quality to the continuous increase of this economic sector. Transforming residues generated by Brazilian agricultural industry and forestry sector into high quality panels is an interesting solution for solving raw material demand problem. The present work aims to show the potential of different types of residues for panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…With regard to the IB property, only the control treatment met the requirements of the standard. These low IB values, regardless of the heat treatment, have also been observed in several studies on bagasse panels 3,9,10 , which is basically owing to the low density of the bagasse material and the consequent need to increase the number of particles to form a panel of predetermined density. This causes an increase in the surface area for the same amount of adhesive, thus more markedly promoting the decrease in the IB property.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…With regard to the IB property, only the control treatment met the requirements of the standard. These low IB values, regardless of the heat treatment, have also been observed in several studies on bagasse panels 3,9,10 , which is basically owing to the low density of the bagasse material and the consequent need to increase the number of particles to form a panel of predetermined density. This causes an increase in the surface area for the same amount of adhesive, thus more markedly promoting the decrease in the IB property.…”
mentioning
confidence: 87%
“…Furthermore, Mendes et al 10 evaluated different types of agricultural and forest residues for particleboard manufacturing and observed WA24h and WA2h values of 12.6% and 60.6%, respectively, for the panels produced with cane bagasse. In general, the results obtained in the present study are below the values found in the literature for particleboard produced from sugarcane bagasse.…”
Section: Temperature (°C) Time (Minutes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these compounds are toxic, which limits the possibility of using SCGs as animal feed. In addition, SCGs contain a high moisture content, which significantly hinders their management, due to putrefaction processes [12] The chemical structure and composition of coffee waste particles is similar to the structure of its beans [13], they are rich in carbohydrates (forming primary structures, i.e. hemicellulose, cellulose, lignin) and so-called secondary structures, i.e.…”
Section: Struktura I Właściwości Lepkosprężystych Pianek Poliuretanowych Napełnionych Fusami Kawymentioning
confidence: 99%
“…Some researchs which had been conducted using sugarcane bagasse in the production of particleboard highlighted its great potential in this field (WIDYORINI et al, 2005;MENDES et al, 2009;XU et al, 2009;BARROS SON et al, 2011;MENDES et al, 2012b). However, in panel production due to its lower density it requires a greater number of bagasse particles, which increases their compressive stresses at the time of pressing, as well as a higher number of hygroscopic sites, thereby making the panel more susceptible to water absorption and dimensional variation than the ones produced by using Pinus and Eucalyptus woods (MENDES et al, 2008).…”
Section: Introductionmentioning
confidence: 99%